2010
DOI: 10.1111/j.1365-2133.2010.09670.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations inEDARADDaccount for a small proportion of hypohidrotic ectodermal dysplasia cases

Abstract: Our study demonstrates that EDARADD mutations are not a frequent cause of HED, while mutations in TRAF6, TAB2 and TAK1 may not be implicated in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
0
19
0
2
Order By: Relevance
“…), 12 no mutations in its human equivalent have been described, excluding a single sequence variant 479T>G (Met160Thr) reported in a patient with HED in whom a pathogenic mutation in EDARADD was detected. However, this sequence abnormality was not responsible for symptoms of HED as it was also present in an asymptomatic brother of the patient 13 …”
Section: Discussionmentioning
confidence: 86%
“…), 12 no mutations in its human equivalent have been described, excluding a single sequence variant 479T>G (Met160Thr) reported in a patient with HED in whom a pathogenic mutation in EDARADD was detected. However, this sequence abnormality was not responsible for symptoms of HED as it was also present in an asymptomatic brother of the patient 13 …”
Section: Discussionmentioning
confidence: 86%
“…To date, four EDARADD mutations have been found in a subset of human HED, one leads to autosomal dominant inheritance (Leu112Arg) [26], while the others lead to autosomal recessive inheritance (Glu142Lys, Pro121Ser, and Thr135-Val136del) [6,28,29]. All of these mutations are located in the DD and functional analyses showed that they resulted in the failure of EDARADD to interact with EDAR and to activate NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the gene encoding the ligand (EDA) are believed to be the most common cause of ED involving the hair, teeth, skin, and sweat glands [Kere et al, 1996;Monreal et al, 1998]. Similar phenotypes are also described in patients with mutations in the EDA receptor (EDAR) gene or, in rare cases, the downstream signaling mediator EDAR-associated death domain (EDARADD) gene [Headon et al, 2001;Chassaing et al, 2006Chassaing et al, , 2010Bailleul-Forestier et al, 2008b;Mikkola 2009]. Mutations in the EDA and EDAR genes have also been shown to cause isolated hypodontia [Tao et al, 2006;Fan et al, 2008;Han et al, 2008;Rasool et al, 2008;Azeem et al, 2009;Mues et al, 2009a;Nieminen, 2009;Song et al, 2009].…”
mentioning
confidence: 94%